2017
DOI: 10.47119/ijrp100119201711
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Job performance: A study on banking sector of Northern region of Sri Lanka

Abstract: Modern day business organizations that are operate in complex and demanding markets are often create stress among its employees. Some argue that a certain level of stress is vital for people to achieve greater heights. Others think they will perform much efficiently if they are allowed to work under minimal stress. However, organizations are designing their job roles to get that extra punch from the human resources; and those who capable of handling such complexities will be rewarded. As such, this study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Based on the results of data processing in the analysis of sub-structure path 2, it was found that the Y variable, namely work stress, significantly affected the variable (Z) the employee performance. This is supported by Jayasinghe and Mendis (2017) where the results state that stress factors such as work, organizational and individual factors have the effect of 52.9% on performance. Stress has an impact on decreasing employee performance as evidenced by the negative relationship between stress and performance.…”
Section: Work Stress (Y) Has a Significant Effect On Employee Perform...mentioning
confidence: 67%
See 1 more Smart Citation
“…Based on the results of data processing in the analysis of sub-structure path 2, it was found that the Y variable, namely work stress, significantly affected the variable (Z) the employee performance. This is supported by Jayasinghe and Mendis (2017) where the results state that stress factors such as work, organizational and individual factors have the effect of 52.9% on performance. Stress has an impact on decreasing employee performance as evidenced by the negative relationship between stress and performance.…”
Section: Work Stress (Y) Has a Significant Effect On Employee Perform...mentioning
confidence: 67%
“…Stress can arise due to pressure or tension that comes from misalignment between a person and his environment, in other words, if the means and demands of the job are not in line with the needs and abilities of a person, then it can be a trigger for stress. This is supported by the research by Jayasinghe and Mendis (2017) on the banking sector in the northern region of Sri Lanka, where the results of the study state that stress factors such as work, organizational and individual factors have an influence of 52.9% on performance. Stress has an impact on decreasing employee performance as evidenced by the negative relationship between stress and performance.…”
Section: Introductionmentioning
confidence: 67%